Diversity in computing majors: how gender, sociability and personality can affect team performance? - Resende, Danilo G.; Berardi, Rita; Gomes-Jr, Luiz (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2024: Anais do XXXV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2024.242231, 2024)
For teams of students to perform most effectively, it is important to understand the patterns related to group formation, including diversity factors. In majors related to computing, this is especially relevant since those are typically less diverse in factors such as gender and social background. This paper explores the association between academic performance and diversity in the context of gender, sociability, and personality. Data on in-class social connections, gender, cross-sectional emotions, team formation, and grades were collected from 15 classes (n = 634) of graduate and undergraduate students of Information Systems, Computer Engineering, and Master's degree in Applied Computing. The influence of each diversity aspect was assessed using linear regression models. Statistical data analysis shows performance improvement for social and personality diversity in teams. The analysis was inconclusive regarding the contribution of gender diversity to the performance of teams.